2020
DOI: 10.21203/rs.2.21239/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of having a baby with cleft lip and palate on parents and on parent-baby relationship: the first French prospective multicentre study

Abstract: Background : The objective of this prospective, multidisciplinary and multicenter study was to explore the effect of a cleft lip, associated or not with a cleft palate, on parents, on parent-infant relationship, and on the baby’s relational development. It also highlighted how the type of cleft and the timing of the surgery could impact this effect. Method : 158 infants, with Cleft lip with or without Palate, and their parents participated in this multicenter prospective cohort. Clinical evaluations were perf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…9 Awareness among the parents and the caregivers is very essential among these patients as this is directly associated with the overall growth and development of the affected infants. 10 Management of cleft lip and palate affected infants requires the parents to acquire certain trained skills which help them to manage the basic needs of the infant. 11,12 Lack of knowledge and awareness and presence of certain myths among parents makes it difficult for them to accept the need of PNAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Awareness among the parents and the caregivers is very essential among these patients as this is directly associated with the overall growth and development of the affected infants. 10 Management of cleft lip and palate affected infants requires the parents to acquire certain trained skills which help them to manage the basic needs of the infant. 11,12 Lack of knowledge and awareness and presence of certain myths among parents makes it difficult for them to accept the need of PNAM.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological distress, helplessness and emotional burden remains extremely high among parents/caregivers of these infants 9 . Awareness among the parents and the caregivers is very essential among these patients as this is directly associated with the overall growth and development of the affected infants 10 …”
Section: Discussionmentioning
confidence: 99%
“…168 One hundred years later, the surgical treatment for cleft palate remains complicated and is still not standardized; debates about technique and the best time to operate are ongoing. 169 Until the late 1990s in Britain, for example, there was a lack of coordination in cleft palate care, which resulted in "suboptimal surgical outcomes, restricted facial growth and poor speech." 170 There was increased safety, certainty, and knowledge in surgical practice throughout the nineteenth and early twentieth centuries, coupled with a rise in confidence in surgery and the surgeon's control over the patient.…”
Section: O N C L U S I O Nmentioning
confidence: 99%
“…Having a baby born with a cleft lip and/or palate (CL/P) can have both social and psychological impacts for parents (Nelson, Glenny et al, 2012). While generally not in the range of clinical distress, research has indicated that parents of children with CL/P may be more likely than the general population to experience parenting stress (Boztepe et al, 2020; Stock et al, 2020), as well as symptoms of post-traumatic stress (Despars et al, 2011) and postpartum depression (Grollemund et al, 2020). Further, parenting a child with CL/P can affect overall familial quality of life (QoL; Antunes et al, 2014; Macho et al, 2017; Emeka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%